Perancangan Sistem Informasi Penjualan Mobil Berbasis Web pada Perusahaan CV. Hijrah Arwindo Mobil - saputra, mahmuda; dewi, ratna (Universitas Gajah Putih, 2025)
The conventional sales model employed by CV. Hijrah Arwindo Mobil has presented significant competitive challenges, primarily due to limited market outreach and operational inefficiencies. This research focuses on the design and implementation of a web-based information system aimed at modernizing the company's car sales process. The system was developed using the Waterfall model, a sequential approach encompassing requirements analysis, system design, implementation, and rigorous testing. Primary data were collected through direct observation and stakeholder interviews. The outcome is a functional web application featuring a public-facing catalog for customers and a secure administrative dashboard for managing vehicle inventory, transactions, and customer data. Validation confirmed that the system operates as specified, successfully transforming business processes, enhancing efficiency, and expanding the company's marketing reach.